Optimalisasi Komunikasi Interpersonal antara Kader Posyandu dan Warga dalam Layanan Kesehatan Masyarakat: Pendekatan Empatik dan Dialogis dalam Penguatan Partisipasi Layanan Kesehatan Berbasis Komunitas - Diah Tri Andini; Istikhana Nurulhuda (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2026)
Posyandu, as a community based health service, faces challenges in the aspect of interpersonal communication between cadres and community members, including the dominance of one-way communication, limited empathy, and the use of less contextual medical terminology. These conditions have contributed to low community participation and reduced trust in health services. This community service program aimed to optimize the interpersonal communication skills of Posyandu Teratai cadres through empathetic, persuasive, and dialogical approaches in order to improve the quality of interaction and community participation. The method employed an educative participatory approach consisting of situation analysis, intervention planning, participatory discussions, communication simulations, and evaluative reflection. The results demonstrated an increased understanding among cadres regarding the importance of empathy, active listening skills, the use of non-judgmental language, and greater confidence in interpersonal interactions. These improvements led to more dialogical two-way communication, greater openness among community members in expressing health-related concerns, and strengthened trust and participation in Posyandu services. The findings confirm that optimizing interpersonal communication plays a strategic role in building trust-based relationships and enhancing the sustainability of community-based health services.